The Community behaviour in reception COVID-19 booster vaccine with a method approach Theory of Planned Behaviour (TPB) in Jambi City - GS, Ressy Elsis; Wijoyo, Yosef (Riset Informasi Kesehatan, 2024)
Background: Coronavirus disease 2019 (COVID-19) is a disease that attacks the respiratory system caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Government has assign a Minister of Health Regulation regarding the Implementation of Vaccinations in the Context of Tackling COVID-19, one of which is the COVID-19 booster vaccine. But, the Community not ready to receive COVID-19 booster vaccine for various reasons.Theory Planned Behaviour (TPB) is a method used to analys peple’s behavior towards receiving the COVID-19 booster vaccine. Method: Quantitative with descriptive design. Independent variables of this research are behaviour belief, subjective Norm and Control belief. And dependent variable in this study is the behavior of receiving the COVID-19 booster vaccine in Jambi City Results: Based on gender, the result were dominated by women 56% in productive age range. Overview of community behaviour in receiving the vaccine using TPB shows infavoriable behavior 54%, Likewise Behavior belief description 55%, Normative belief is 73% and good description Control belief in receiving COVID-19 booster vaccine is 73%. Conclusion: Based on the research that has been carried out, Consructs contained in TPB are suitable for use in research to behavior. But, individual studies may show varying result across geographic regions and study population.